Early Hemodynamic Disorders and Their Association with the Development of Acute Pulmonary Lesion in Severe Concomitant Injury - V. V. Moroz; A. M. Golubev; D. V. Lysenko; G. N. Meshcheryakov (Общая реаниматология, 2005)
Early changes in the parameters of central hemodynamics and pulmonary extravascular fluid were studied in patients who had sustained a severe concomitant injury in combination with acute massive blood loss. Early postoperative monitoring of these parameters by a «Pulsion Picco Plus» invasive monitoring apparatus was ascertained to verify the early stages on non-cardiogenic pulmonary edema, to assess a risk for acute lung lesion and acute respiratory distress syndrome in the phase of reperfusion lesions, and to perform an adequate correction of therapy.